Continuing Professional Development in Health and Social Care : Strategies for Lifelong Learning - Alsop, Auldeen (Chichester, West Sussex : Wiley-Blackwell, 2013)
This new edition of the basic resource has been substantially restructured and updated to reflect the very latest CPD requirements and includes several new chapters. It reviews current policy on CPD and discusses the theoretical basis for maintaining competence and for adult learning, whilst providing practical guidance on how to develop a strategy for professional and career development, and on portfolio preparation that shows evidence of professional updating and CPD.
Lifelong learning and continuing professional development -- Regulation of allied health and social care professionals -- The professional portfolio -- The process of continuing professional development -- Learning to learn -- Learning with others -- Learning in the workplace -- Scholarly activity and research for the practitioner -- Learning to write and writing to learn -- Career development -- CPD and career development for academics -- Leadership and professional development -- Learning strategies and CPD for support workers -- Learning for leisure and pleasure.
Includes bibliographical references and index.
Print version record.
Keywords: Allied health personnel -- Training of; Social workers -- Training of; Social service -- Study and teaching (Continuing education); Allied Health Personnel -- education; Education, Continuing; Professional Competence; MEDICAL -- Allied Health Services -- Occupational Therapy; Continuing education; Paramedical education; Electronic books; Electronic books; Electronic books